Habitual physical activity patterns of pre-school children from Bragança - Magalhães, Pedro (2022)
The increase in the prevalence of overweight in children is commonly associated with their low levels of physical activity (PA). In fact, young people who have higher levels of PA over several years tend to have lower rates of overweight than their less active peers. Thus, it becomes of the utmost importance to promote the practice of regular PA among children. In this context, the aims of this study were to compare the number of steps done by children during the weekdays with the weekend and to analyse the contribution of a schoolbase physical exercise (PE) session to the total number of daily steps performed by children. The sample comprised 105 pre-school children, from 3 to 6 years old (4.48±0.69) from 5 kindergartens from Bragança. The PA evaluation was done through daily number of steps from New-Lifestyles NL-2000 pedometer. The mean number of steps taken by the children remained relatively constant during the week, decreasing only slightly on Friday. However, on Saturday and Sunday the decline was more pronounced. Significant differences were found between the number of steps on weekdays and weekend days (p<0.001), with higher levels of PA on weekdays. PA was higher (p<0.001) on the days with PE session than without PE session in kindergarten. Children of preschool age are more active during the weekdays than at the weekend. The implementation at school-based of PE session at pre-school level had a significant impact on daily PA levels of the children.